Rasch validation of the Arabic version of the beach center family quality of life scale (BCFQOL-AR) - Alnahdi, Ghaleb Hamad (Frontiers in Psychology, 2022)
Aim This study aimed to examine the dimensionality of the BCFQOL-AR using Rasch analysis. Method The sample consisted of 320 families having a member with intellectual or developmental disabilities. Rasch analysis was used to validate the dimensionality of the scale. The participants were from Riyadh, Saudi Arabia. Results The BCFQOL-AR 25-item scale was multidimensional. Rasch analyses support the unidimensionality of the five subscales. There were no indicators of differential item function for any of the items, regardless of sex or age. Conclusion The BCFQOL-AR is a multidimensional scale that measures families with members who are satisfied with their quality of life. Therefore, obtaining a total score at the subscale level is supported and showed that each of the five subscales of the BCFQOL can be used alone. This study partially supports the practices used with other versions of the scale, by providing the statistical base, where means were used at the subscale level in different countries.